Balloon-occluded retrograde transvenous obliteration for six consecutive patients with duodenal varices - Shiro Miyayama; Masashi Yamashiro; Rie Ikeda; Junichi Matsumoto; Nobuhiko Ogawa; Kazuo Notsumata (Society of Gastrointestinal Intervention, 2022)
Background : : Bleeding from duodenal varices is a rare but life-threatening complication of portal hypertension. The treatment of duodenal varices remains difficult and a definitive treatment strategy has not been established. The aim of this study was to report the technical aspects and outcomes of balloon-occluded retrograde transvenous obliteration (BRTO) using 5% ethanolamine oleate with iopamidol (EOI) for duodenal varices. Methods : : Six consecutive patients with duodenal varices treated using BRTO were eligible. Endoscopic treatment was performed first in three patients with active bleeding. After coil embolization of collateral veins, stepwise EOI infusion was performed at intervals of 10-30 minutes under balloon occlusion until the main efferent vein, varices, and the main afferent vein were filled with EOI and clots. The techniques and outcomes of BRTO were retrospectively evaluated. Results : : The main efferent vein of duodenal varices was the right (n = 4) or left (n = 2) gonadal vein. In three patients with ruptured varices, BRTO was performed after achieving hemostasis by endoscopic treatment. In five patients, 1-4 (mean, 2.4 ± 1.1) collateral veins were embolized with coils before EOI infusion. Furthermore, 11-21 mL (mean, 15.3 ± 4.2 mL) of EOI was infused by 3-5 (mean, 3.5 ± 1.0) stepwise infusions via the efferent vein under balloon occlusion. The duration of EOI infusion under balloon occlusion ranged from 82 to 118 minutes (mean, 87.8 ± 13.6 minutes). The varices were thrombosed in all but one patient. In the remaining patient, the varices were thrombosed by additional BRTO under overnight balloon occlusion performed 19 days later. The only complications were a transient fever and hematuria. All duodenal varices disappeared during a followup of 4-32 months (mean, 16.2 ± 11.1 months) after BRTO. Conclusion : : BRTO using EOI is an effective treatment for duodenal varices.